Implementasi Program Inkubator Nazhir di Yayasan Edukasi Wakaf Indonesia Yogyakarta - Paridi, Saniyah Ashari; Rofi'i, Rofi'i; Widagdo, Haidi Hajar (Universitas Islam Negeri Alauddin Makassar, 2024)
This research was conducted to analyze the implementation, management of Human Resources and the problems of the Nazir incubator program. This research is a type of qualitative research with a descriptive nature. The type of research used in this research is Field Research, or field research. The research was carried out at the Indonesian Waqf Education Foundation (YEWI). The data sources in this research come from primary data obtained from all informants related to the management of the Nazir incubator and secondary data obtained from various existing sources such as books, reports, and so on. The first stage of the data analysis technique is collecting data from various sources and relevant research results. After the data is collected, the next step is data reduction, where significant information is identified and separated from the irrelevant. This process ensures that only essential data is retained for further analysis. After data reduction, the data presentation stage begins. It involves careful interpretation of the reduced data and presentation of the information in the form of clear and scientific words or sentences. It is important to present data objectively, without hiding any shortcomings or ambiguities that may exist. Finally, conclusions are drawn based on data reduction and information presentation. The incubator program in the waqf program is designed to create professional nazhir candidates with the aim of creating the potential for nazhir candidates to develop skills in waqf management. In the context of resource management, the Nazhir incubator program is designed to assist Nazhirs in managing resources related to the waqf they handle, so that all existing resources become much more organized, starting from administration to collecting cash waqf.